COVID Academic Pandemic: Techno Stress Faced by Teaching Staff for Online Academic Activities - Zheng, Mao; Asif, Muhammad; Tufail, Muhammad Shahid; Naseer, Saira; Khokhar, Shahid Ghafoor; Chen, Xiding; Naveed, Rana Tahir (Frontiers in Psychology, 2022)
This paper analyzes the impact of the COVID-19 pandemic on the mental health of the teachers, specifically the technostress arising in them as a result of issues faced by them in the use of technology when they conduct the online academic activities. It aims to assess the major factors related to online teaching that specifically adds to technostress on the teachers during the COVID-19 outbreak. Finally, the study aims to provide suggestions to the policymakers and the management of the universities so that the effect of the COVID-19s on teachers’ mental health and the related technostress can be reduced. This paper is a literature review of the articles on the notion of technostress of teachers and their mental health by searching the related articles with these terminologies using the renowned search engines of Google scholar and Web of Science. A combination of the terms, like Coronavirus, COVID-19, mental health, psychological distress, technostress, and online teaching were used in the article search for the review. The literature has suggested that the COVID-19 outbreak has significantly affected the mental health of the employees in general and specifically, the teachers who are engaged in online academic activities and teaching in the universities. The paper has identified a few factors that are the cause of the technostress and provides recommendations for the university management and the policymakers for minimizing their negative impact on the teachers, in terms of the technostress and their mental health. Coronavirus is a new strain of viruses that has badly engulfed the entire population of the world. It is even now badly rising and causing deaths while this article is in the writing phase. The paper has addressed the mental health concerns of the university teachers as they are now working from home using ICT for delivering the lectures and conducting the online teaching and learning activities for the students of their universities. This is a matter of grave importance now and requires immediate attention. Hence, this paper broadens the scope of the research on coronavirus and its impact on university teachers.